Synthesis of Cytotoxic Palmerolides - Lisboa, Marilda P.; Dudley, Gregory B. (Chemistry : a European journal, 2013)
The chemical synthesis of the palmerolides is the subject of this review. The palmerolides are a family of Antarctic marine natural products, many of which display potent and selective cytotoxicity against melanoma cells. The confluence of promising bioactivities, limited natural supplies, and complex structures makes the palmerolides exciting targets for chemical synthesis. To date, several approaches have been reported, and a consensus strategy based on convergent fragment assembly has emerged. Collective wisdom from myriad approaches reviewed here may enable hybrid strategies capable of delivering larger amounts of synthetic palmerolides to support continued biological studies. Considering the relative lack of options for melanoma chemotherapy and the intriguing activity profile of the palmerolides, efforts aimed at developing an efficient, gram‐scale synthesis of palmerolide A and congeneric structures should be given a high priority. Can synthesis deliver? Chemical synthesis is the key to unlocking the chemotherapeutic potential of the palmerolides. This review covers the chemistry and biology of the palmerolides through early 2013, highlighting the evolution of a consensus strategy that could lead to cost‐effective production of synthetic palmerolides. Palmerolide A is potently and selectively cytotoxic to certain melanomas. Its mechanism of action is poorly understood but likely involves inhibition of a transmembrane proton pump involved in regulation of cellular pH and metastasis.